Principal Leadership in Partnership Development in Early Childhood Institutions - Nur Oktaviani, Mustika; Aslamiah, Aslamiah; Effendi, Rustam; Cinantya, Cellia (Journal of English Language and Education, 2025)
The leadership of school principals plays a crucial role in fostering effective school partnerships. This article aims to discuss the importance of school principals' leadership in building collaborative relationships with various stakeholders, including parents, the community, and government institutions, to support the improvement of education quality. In addition, the article also explores the strategies implemented by school principals to strengthen partnerships, such as the development of joint programs, stakeholder involvement in decision-making, and transparent resource management. The research method used in this article is a descriptive qualitative approach. The findings indicate that the principal plays a key role in building relationships among the school, teachers, and the community to enhance the quality of education at TK Negeri Pembina Banjarmasin Utara 2. With strong partnerships, schools are not only able to improve the quality of education but also strengthen their connections with the social environment. This article provides practical insights for school principals in optimizing their role as leaders who are focused on developing effective school partnerships